BTEX detection with composites of ethylenevinyl acetate and nanostructured carbon - Stepina, Santa; Berzina, Astrida; Sakale, Gita; Knite, Maris (Beilstein Journal of Nanotechnology, 2017)
By using a solvent-based method composites of ethylenevinyl acetate copolymer and carbon black (EVA–CB) were synthesized for sensing BTEX (benzene, toluene, ethylbenzene and xylene) vapours. The composites were characterized using atomic force microscopy (AFM) in an electroconductive mode. Gas sensing results show that EVA-CB can reproducibly detect BTEX and that the response increases linearly with vapour concentration. Compared to gas-sensing measurements of gasoline vapours, the responses with toluene and ethylbenzene are different and can be explained by varying side chains of the benzene ring.
Keywords: benzene detection; polymer–nanostructured carbon composites; volatile organic compound (VOC) sensors